2019
DOI: 10.1167/iovs.18-26079
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Lifetimes in Patients With Hydroxychloroquine Retinopathy

Abstract: PURPOSE. To investigate fundus autofluorescence lifetime features in patients with hydroxychloroquine (HCQ) retinopathy, and to identify early markers of retinal alterations in patients due to HCQ. METHODS. Patients attending screening for HCQ retinopathy were imaged with a fluorescence lifetime imaging ophthalmoscope. Mean retinal fluorescence lifetimes (Tm) were obtained in a short spectral channel (SSC, 498-560 nm) and a long spectral channel (LSC, 560-720 nm). Screening modalities included fundus images, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
(45 reference statements)
1
14
0
5
Order By: Relevance
“…Recently, several groups reported prolonged lifetimes at the parafoveal region in patients with HCQ retinal toxicity. 46,70 However, whether FLIO could be a screening tool for early detection of CQ/HCQ induced maculopathy is still controversially discussed. 46,70 So far, in QAF studies, QAF8 (eight segments from a projected analysis grid, centered on the fovea, as introduced by Greenberg et al 31 ) was used for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several groups reported prolonged lifetimes at the parafoveal region in patients with HCQ retinal toxicity. 46,70 However, whether FLIO could be a screening tool for early detection of CQ/HCQ induced maculopathy is still controversially discussed. 46,70 So far, in QAF studies, QAF8 (eight segments from a projected analysis grid, centered on the fovea, as introduced by Greenberg et al 31 ) was used for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…46,70 However, whether FLIO could be a screening tool for early detection of CQ/HCQ induced maculopathy is still controversially discussed. 46,70 So far, in QAF studies, QAF8 (eight segments from a projected analysis grid, centered on the fovea, as introduced by Greenberg et al 31 ) was used for analysis. As shown in our study, especially in the maculopathy patients, QAF8 analysis does not capture the affected areas and more flexible analysis patterns (narrowing of the analysis field, flexible dimensions, free hand tools) are warranted to specifically analyze the respective areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Patients with HCQ retinopathy also exhibit significantly prolonged mean fluorescence lifetimes within the parafoveal area. 15 Early studies of CQ, the related drug, revealed that as a weak base, it accumulates in lysosomes. 16 Based on research in animals and cellular assays, it was also suggested that HCQ toxicity begins in RPE cells.…”
mentioning
confidence: 99%
“… 14 Patients with HCQ retinopathy also exhibit significantly prolonged mean fluorescence lifetimes within the parafoveal area. 15 …”
mentioning
confidence: 99%